Design of Low Complexity Robust Broadband Beamformers with Least Squared Performance Criterion - Rimantho, Dedi; Dam, Hai Huyen (Heidi); Nordholm, Sven (AITAC, 2012)
This paper investigates the design of low complexity, non-robust and robust broadband beamformers with least squared criterion. An iterative algorithm is proposed to reduce the number of non-zero coefficients in both the non-robust and robust beamformers to reduce the computational complexity. Design examples show that the number of nonzero coefficients for the beamformers can be significantly reduced without a significant degradation in the integral squared error. In addition, the robust beamformer is less sensitive to non-zero coefficient reduction than the non-robust beamformer. In particular, the number of non-zero coefficients for the robust beamformer can be reduced by up to 74% with only a small reduction of 1.34dB in the integral squared error.